The beginning of a large-scale political reform in Russia: a new turn in 2020 - Inna A. Vetrenko (Правоприменение)
The subject. The article is devoted to the analysis of the draft political and constitutional reform that was announced in the last Presidential Address to the Federal Assembly at January 15, 2020. The purpose of the article is to try to predict the positive and negative consequences of changing the legal status of the highest Russian authorities.The methodology of the study includes analysis and interpretation of Presidential Addresses to the Federal Assembly and Russian Constitution as well as dialectical approach and methods of political science.The main results and scope of their application. For a long time there was a clear request for changes in the government, and various expert platforms discussed issues related to changing the Constitution of the Russian Federation, which was adopted at a national referendum in December 1993.On January 15, 2020, Vladimir Putin addressed his 16th message to the Parliament. In accordance with the Constitution, the President of Russia annually addresses the Federal Assembly with a message on the situation in the country and on the main directions of domestic and foreign policy. The last address turned out to be a landmark and historical one, as it announced the main provisions of the upcoming large-scale political and constitutional reform in Russia. Heads of constituent entities, members of the State Duma and the Federation Council, Prime Minister and Deputy Prime Ministers, Federal Ministers, heads of Federal bodies, judges will no longer be able to have foreign citizenship or a foreign residence permit. He proposed even more stringent requirements for a candidate for the post of Pres-ident: no foreign citizenship or residence permit even in the past, as well as permanent residence in Russia for at least 25 years. The position of the State Council is being strength-ened and it is reflected in the Constitution of the Russian Federation as an institution of power in the country. The position of the Federal Assembly is strengthened by the fact that the Parliament is given the right to approve the candidacy of the Prime Minister, as well as all Deputy Prime Ministers and Federal Ministers. The status of local self-government and the role of governors in the regions is being raised. The main reason for the reform is the desire to reduce the powers of the President and transfer part of them to the Parliament, so that the next President is no longer endowed with virtually absolute power, and, in turn, can not initiate another reform without the ap-proval of all branches of government. The author of the article identifies the reasons for the political reform and gives forecasts for the future after its implementation. Conclusions. The author links these changes to the upcoming transfer of presidential power after 2024. The reform does not mean the transition of the Russian Federation to a parliamentary republic, since the head of state retains the status of a key figure in the political system, and it is he who has concentrated key functions. Fixing a number of social obligations in the Constitution in terms of salaries and pensions will not have a significant impact on the socio-economic situation.